Video-based Parkinson's disease assessments in a nationwide cohort of Fox Insight participants. (2021) - Myers, Taylor L.; Tarolli, Christopher G.; Adams, Jamie L.; Barbano, Richard; Cristina Gil-Díaz, María; Spear, Kelsey L.; Lowell, Jill; Daeschler, Margaret; Riley, Lindsey; Amondikar, Ninad; Auinger, Peggy; Marras, Connie; et al.
Highlights: Self-reported Parkinson's disease diagnosis is accurate in Fox Insight. Single-site virtual research studies can efficiently recruit large national cohorts. Participants are satisfied with and interested in future virtual research studies. Abstract: Introduction: Parkinson's disease (PD) research is hampered by slow, inefficient recruitment and burdensome in-person assessments that may be challenging to conduct in a world affected by COVID-19. Fox Insight is an ongoing prospective clinical research study that enables individuals to participate in clinical research from their own homes by completing online questionnaires. To date, over 45, 000 participants with and without PD have enrolled. We sought to validate self-reported PD diagnosis in the Fox Insight cohort, assess the validity of other self-reported health information, and evaluate the willingness of participants to participate in video-based research studies. Methods: Individuals with and without self-reported PD enrolled in Fox Insight were invited to participate in this virtual research study. Participants completed online questionnaires and two virtual visits, during which we conducted standard cognitive and motor assessments. A movement disorder expert determined the most likely diagnosis, which was compared to self-reported diagnosis. Results: A total of 203 participants from 40 U.S. states, 159 with remote clinician-determined PD and 44 without, completed the study (59% male, mean (SD) age 65.7 (9.8)). Level of agreement between self-reported PD diagnosis in Fox Insight and clinician-determined diagnosis was very good ((kappa = 0.85, 95% CI 0.76–0.94). Overall, 97.9% of participants were satisfied with the study, 98.5% were willing to participate in a future observational study with virtual visits, and 76.1% were willing to participate in an interventional trial with virtual visits. Conclusion: Among the Fox Insight cohort, self-reported diagnosis is accurate and interest in virtual research studies is high.